Design of a mixed ℋ2/ℋ∞ gain scheduling state derivative feedback controller for linear parameter-varying systems - Beteto, Marco Antonio Leite [UNESP]; Assunção, Edvaldo [UNESP]; Teixeira, Marcelo Carvalho Minhoto [UNESP] (Taylor & Francis, 2023)
In this paper, the mixed (Formula presented.) guaranteed cost for continuous-time linear parameter-varying (LPV) systems is proposed. In addition, the gain scheduling (GS) strategy and the state derivative feedback (SDF) were considered. The time-varying parameter is assumed to be available for online measurement, and the conditions are based on linear matrix inequalities (LMIs). To improve the behaviour of the system, the (Formula presented.) -stability is used. Examples show that the proposed conditions achieved good results in reducing the disturbance effect in the system. Furthermore, with the proposed methods, it is possible to guarantee the asymptotic stability and a mixed (Formula presented.) guaranteed cost minimisation.
Keywords: stability; gain scheduling (GS); guaranteed cost; linear matrix inequalities (LMIs); linear parameter-varying (LPV) systems; state derivative feedback (SDF)